PELATIHAN PEMBUATAN STIK RUMPUT LAUT Kappaphycus alvarezii DALAM RANGKA MENDUKUNG IMPLEMENTASI EKONOMI BIRU DI KELOMPOK MASYARAKAT PESISIR DI DESA KALIUDA - Henggu, Krisman Umbu; Katonguretang, Elfis Umbu; Nggaba, Mayun Erawati; Radjah, Yudha Gustial; Mehakati, Imanuel Umbu Taralandu; Nasution, Nur Azizah (Universitas Mataram, 2024)
Kaliuda Village is one of the coastal villages in East Sumba Regency, which is the largest producer of Kappaphycus alvarezii seaweed in the region. However, the coastal community’s knowledge regarding the diversification of seaweed into various food products remains limited. This is evident in the case of dried seaweed, which is primarily intended for industrial use, and rejected seaweed that companies do not utilize or process. The aim is to conduct training and mentoring activities to enhance community knowledge about utilizing seaweed as a food source through diversification. Additionally, the community will gain an understanding of business strategies related to processed seaweed products. The community engagement activities employ the Participatory Rural Appraisal (PRA) approach, involving education, mentoring, and training. Education sessions cover seaweed diversification and business development. Furthermore, the process includes mentoring and training in making seaweed sticks from Kappaphycus alvarezii. A total of 34 coastal community members participated in these activities. The engagement began with presentations on the potential development of Kappaphycus alvarezii, marketing strategies for processed seaweed products (including market opportunities and competitors), pivot strategies, and the use of e-commerce digitalization. In addition to the presentations, the coastal community received training and guidance on seaweed stick production. The training covered raw material preparation, dough-making, molding, frying, and packaging. The high level of community participation significantly supported the success of this engagement. During the activities, the PKM team engaged in discussions to identify challenges and alternative solutions. The partners’ response to the presentation of educational materials, mentoring, and training falls within the satisfied to very satisfied category. The recommended suggestion is that the seaweed processed product diversification group should receive support from the village government.